2022
DOI: 10.1186/s10194-022-01471-3
|View full text |Cite|
|
Sign up to set email alerts
|

Applying a biopsychosocial model to migraine: rationale and clinical implications

Abstract: Migraine is a complex condition in which genetic predisposition interacts with other biological and environmental factors determining its course. A hyperresponsive brain cortex, peripheral and central alterations in pain processing, and comorbidities play a role from an individual biological standpoint. Besides, dysfunctional psychological mechanisms, social and lifestyle factors may intervene and impact on the clinical phenotype of the disease, promote its transformation from episodic into chronic migraine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 199 publications
1
34
0
Order By: Relevance
“…In light of the results of the literature studies and our findings, we think that evaluation and treatment methods may need to be shaped differently. In addition to drug therapy, patients can be given patient and pain education [ 34 ], a biopsychosocial model can be applied [ 35 ] or physical therapy and rehabilitation practices can be recommended [ 36 ]. Rezaeian et al evaluated migraine patients in two groups as treatment and control groups and used myofascial release and stretching methods in the treatment group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of the results of the literature studies and our findings, we think that evaluation and treatment methods may need to be shaped differently. In addition to drug therapy, patients can be given patient and pain education [ 34 ], a biopsychosocial model can be applied [ 35 ] or physical therapy and rehabilitation practices can be recommended [ 36 ]. Rezaeian et al evaluated migraine patients in two groups as treatment and control groups and used myofascial release and stretching methods in the treatment group.…”
Section: Discussionmentioning
confidence: 99%
“…In future studies, this situation can be generalized with different clinics and sample sizes. Finally, while NDI evaluates activities that require strength and stability, it also evaluates concentration and pain parameters, which can be affected by psychological, social, and work conditions [ 35 , 38 ]. Since our study was a retrospective study, we could not evaluate psychological, social, and work conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Migraines arise out of the interaction between biological mechanisms, environmental and lifestyle issues, and psychological factors [ 7 ]. Examples of the first include genetic predisposition and comorbidities [ 8 ], which support the use of medications for prophylaxis and acute treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, many studies compared mindfulness against waitlist, i.e., to non-treatment, which is clearly not what would be undertaken in standard practice. As previously stated, migraines (including CM-MOH) require a biopsychosocial approach in which biological mechanisms, environmental and lifestyle issues, and psychological factors are jointly addressed [ 7 ]. In a pilot non-randomized study, we showed that the 12-month course of headache frequency and medication intake in patients with CM and MOH, was similar between patients under pharmacological prophylaxis only and patients attending six mindfulness-based sessions only [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following the publication of the original article [ 1 ], we were notified that the arrows displayed in Fig. 4 were misaligned in the pdf version of the paper.…”
mentioning
confidence: 99%